Service Quality and Customer Loyalty: The Mediating Role of Customer Satisfaction in Cafe’s - Sulistiowati; Supriyanto, Antok; Erstiawan, Martinus Sony; Soebijono, Tony; Angesti, Dyan (GREENOMIKA, 2025)
This study examines the effect of service quality on customer satisfaction and loyalty in the cafe industry in Surabaya, with a focus on the mediating role of customer satisfaction. In this increasingly competitive industry, cafe managers must pay attention to service quality to maintain loyal customers. Based on the Servqual conceptual model which includes the dimensions of tangibles, reliability, responsiveness, assurance, and empathy, this study aims to influence service quality on customer loyalty as a mediating variable and identify the most significant Servqual dimensions. Using quantitative methods with Structural Equation Modeling (SEM-PLS) analysis, data was collected through questionnaires distributed to 120 cafe visitors. The results showed that the dimensions of tangibles, reliability, assurance, and empathy had a positive and significant effect on customer satisfaction, while responsiveness showed no significant effect. In addition, customer satisfaction is proven to have a strong influence on customer loyalty. The conclusion of this study is that cafe managers need to focus on improving service quality that can create customer satisfaction, so that it can influence customer loyalty and support the sustainability of the cafe business.